Tailoring effective requirement’s specification for ingenuity in Software Development Life Cycle. - et.al, Naveen N Kulkarni (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Software Requirements Engineering (SRE) process define software manuscripts with sustaining Software Requirement Specification (SRS) and its activities. SRE comprises many tasks requirement analysis, elicitation, documentation, conciliation and validation. Natural language is most popular and commonly used to form the SRS document. However, natural language has its own limitations wrt quality approach for SRS. The constraints include incomplete, incorrect, ambiguous, and inconsistency. In software engineering, most applications are object-oriented. So requirements are unlike problem domain need to be developed. So software documentation is completed in such a way that, all authorized users like clients, analysts, managers, and developers can understand it. These are the basis for success of any planned project. Most of the work is still dependent on intensive human (domain expert) work. consequences of the project success still depend on timeliness with tending errors. The fundamental quality intended for each activity is specified during the software development process. This paper concludes critically with best practices in writing SRS. This approach helps to mitigate SRS limitation up to some extent. An initial review highlights capable results for the proposed practices